Eine Methode zur Unterstützung der disziplinübergreifenden Zusammenarbeit in der Produktentwicklung auf Grundlage einer integrierten Visualisierung konzeptioneller Modelle - Herter, Johannes (KIT Scientific Publishing, 2017)
Industrial product development requires close collaboration between experts of several disciplines. Misunderstandings and discussions are inevitable. An integrated visualization of discipline specific conceptual models can foster agreement between experts. This work introduces a three dimensional visualization for integrated conceptual models. Models are arranged in a common 3-D information space. Dependencies are visible and provide a means for interdisciplinary problem solving.